Study of Effect of Sweet Basil (Ocimum basilicum Linn) Essential Oil at Various Dosages on Estrus cycle of Sprague-Dawley Rats - Cornelius Prabahari Cahyo Putro (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
The objective of this research was to identify the effect of various dosages of sweet basil essential oil in estrus cycle of Sprague-Dawley rats. Twenty four healthy female of Sprague-Dawley rats, with the age of 2 month, 120-140 gr of body weight were used in this experiment. After estrus synchronization using Whitten effect, the rats were divided randomly into 4 groups, such as groups I, II, III and IV, treated with dosages of ½ x, x, and 2x, while the control rats were given extract solvent of 5% polyethylene glycol. Vaginal smears and Giemsa staining were used to determine each estrus cycle phase. Each estrus cycle could be distinguished according to type of cells appeared in preparation of vaginal smears under microscope with 40x. The change of duration of estrus cycle everyday (proestrus, estrus, metestrus, and diestrus) was recorded. The result indicated phase of proestrus had the longest change in time (2.43±0.54 days in x dosage), while for control: 1.23±0.47, 0.5x dosage: 2.02±0.41 and 2x dosage: 1.98±0.28. In estrus phase, the longest phase was 2.10±0.46 at 2x dosage, while other phase durations for control, 0.5 dosage and x dosage were 1.65±0.35, 1.87±0.37 and 1.90±0.27, respectively. The result also indicated that duration of proestrus was significantly different compared to others (P<0,05). Based on this result, it could be conclouded sweet basil essential oil can affect duration of estrus cycle in Sprague-Dawley rats, especially proestrus (P<0,05).Keywords: sweet basil essential oil, estrus cycle, vaginal smear, Sprague-Dawley rats, proestrus